2014
DOI: 10.4236/ajps.2014.525387
|View full text |Cite
|
Sign up to set email alerts
|

Inductors of Resistance and Their Role in Photosynthesis and Antioxidant System Activity of Coffee Seedlings

Abstract: We investigated the effects of formulations based on phosphite products on gas exchange and activity of antioxidant enzymes in coffee plants. Seedlings of the Mundo Novo cultivar were submitted to various treatments composed of different formulations of with potassium phosphite (ADB 120), manganese phosphite (Reforce Mn), and fungicide (PrioriXtra ® ). For coffee seedlings, the combination of potassium phosphite and citrus by-products, isolated or in a combination with other products elicited the antioxidant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…These enzymes clean ROS and protect cells from oxidative damage (Hossain and Uddin 2011). Fernandes et al (2014) found increased activity in SOD, CAT and APX enzymes in coffee seedlings after MnPhi spraying in the absence of pathogen. The current study showed that MnPhi induced increase in SOD and APX activity in leaves of coffee seedlings after infection with H. vastatrix.…”
Section: Discussionmentioning
confidence: 82%
“…These enzymes clean ROS and protect cells from oxidative damage (Hossain and Uddin 2011). Fernandes et al (2014) found increased activity in SOD, CAT and APX enzymes in coffee seedlings after MnPhi spraying in the absence of pathogen. The current study showed that MnPhi induced increase in SOD and APX activity in leaves of coffee seedlings after infection with H. vastatrix.…”
Section: Discussionmentioning
confidence: 82%
“…In coffee leaves treated with phosphites (inorganic salts of phosphorous acid), the induction of the expression of defense-related genes, such as peroxidase, catalase, β-1.3glucanase and PAL, was reported [199]. Biochemical studies further confirmed the increase in the activity of antioxidant enzymes (ascorbate peroxidase, superoxide dismutase, catalase and polyphenol oxidase) [199,204] and the photosynthetic rates of treated leaves [204]. Recently, a physiological (leaf gas-exchange), biochemical (enzymatic) and proteomic study was undertaken.…”
Section: Systemic-acquired Resistance (Sar) In Coffeementioning
confidence: 90%
“…Phi supplementation in citrus byproducts regulates the antioxidant system by increasing the activity of SOD, CAT, and APX after four treatments on coffee seedlings. In addition, increasing the antioxidant content continuously evolves in defense of the PS electron transport chain by maintaining better levels of the NADP + and inhibiting the composition of toxic radicals ( Fernandes et al, 2014 ). These results show that proper use of Phi can be useful to improve the antioxidant defense mechanism of plants under pathogen stress.…”
Section: Phi-triggered Plant Defense Response Against Biotic Stressesmentioning
confidence: 99%